Aquatic Plyometric Training (APT) terhadap Peningkatkan Tinggi Loncatan Spike pada Pemain Bola Voli - Siti Nurmala; Dikdik Zafar Sidik; Yopi Kusdinar; Pipit Pitriani (Universitas Negeri Semarang, 2024)
Spike or often called smash is one of the basic techniques in playing volleyball. Spike/smash in volleyball plays a very important role in a team's success, especially when attacking. This research aims to determine the effect of Aquatic Plyometric Training (APT) on increasing Spike jump height in Volleyball players. The method used in this research was an experimental method where APT was given twice a week, for 6 weeks, with training in the form of squat jumps with blocking form, single- and double-leg bounding, spike approaches, depth jumps, power skips, and continuous jumping for height. Using a one group pre-test post-test research design. The population in this study was 25 female volleyball athletes from SMAN 1 Kawali. The sampling method used purposive sampling, which obtained 10 samples according to the criteria. The research instrument used to measure jump height is the Vertical jump. The results of this study state that there is a significant influence of Aquatic Plyometric Training (APT) on increasing spike jump height in volleyball players. So it can be concluded that to increase the height of the spike jump, you can train using Aquatic Plyometric Training.